Case of Hypopigmented Mycosis Fungoides: Clinical and Pathological Discrimination from Mimicking Conditions - Mimanda, Suci Leni; Ennesta Asri; Indah Indria Sari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Hypopigmented mycosis fungoides (HMF) is an uncommon variant of mycosis fungoides (MF), a cutaneous T-cell lymphoma. It presents a diagnostic challenge due to its clinical resemblance to various benign dermatological conditions. This case report highlights the importance of a comprehensive approach to diagnosis, incorporating clinical, histopathological, and immunohistochemical findings. Case presentation: A 48-year-old Indonesian woman presented with a one-year history of progressive, asymptomatic hypopigmented patches on her extremities. Initially misdiagnosed as progressive macular hypomelanosis, the patient's condition did not improve with topical treatments. Clinical examination revealed multiple hypopigmented patches and macules on both extremities, with some lesions exhibiting fine scales. Histopathological examination demonstrated atypical lymphocytes with epidermotropism and Pautrier's microabscesses. Immunohistochemical staining confirmed the presence of CD3+ T-cells, leading to the diagnosis of HMF. Conclusion: HMF can mimic various dermatological conditions, making diagnosis challenging. A thorough clinical assessment, coupled with histopathological and immunohistochemical evaluation, is crucial for accurate diagnosis and appropriate management. This case underscores the importance of considering HMF in the differential diagnosis of hypopigmented skin lesions, particularly in individuals with persistent or atypical presentations. Early recognition and intervention are essential for optimizing patient outcomes.